The problem and challenges faced by Sarawak handicraft entrepreneurs - Jemat, Mohammad Zain; Durin, Anna; Tugang, Noria (2014)
This study briefly discussed about the problem and challenges faced by Sarawak handicraft entrepreneurs such as forest-based products, textile products, metal-based products, ceramic products and assorted crafts in the state.It is based on my research carried out in the year 2011 till 2012.Most entrepreneurs that are involved in this research were registered under Perbadanan Kemajuan Kraftangan Sarawak and Sarawak Craft Council by making handicrafts-as full-time or part-time jobs. Some of them have been identified actively producing handicrafts in a big and small scale.Nevertheless, to develop and expand their products in the market, they encounter several problems and challenges, relatively to the lack of raw materials.This has been a very common issue highlighted by the entrepreneurs during this research is conducted since 2011. Besides that, few of the handicraft entrepreneurs in Sarawak have been identified to face with the lack of capital, long time of product completion, inadequate of technological equipment, market and customer demand, and so forth.